Reconstruction of Educational Science With Prophetic Paradigm in Faculty of Tarbiyah at IAI Muhammadiyah Bima - Ruslan Ruslan; Luthfiyah Luthfiyah (IAIN Ponorogo, 2020)
The Tarbiyah Faculty of IAI Muhammadiyah Bima still uses educational science reference books, which nota bene does not contain prophetic elements explicitly. Reference books are students’ reference source to discover their knowledge, enrich the treasure of scholarly, and construct their thinking paradigm. This research aims to develop Educational Science reference by integrating prophetic values. This library research used philosophical and sociological approaches. The data source were educational science books, prophetic books, and others. The results showed that the reconstruction of educational science reference books by prophetic values construct civilized man, educated and well behaved as a humanist. It also optimized students’ critical and creative capacity, delivering the thinking system from the shackles of culture and tradition, class and sex dominations, and eliminating the oppression. Transcendentally construct their inners as God creatures who have to be responsible for themselves, their society, and nature. It has to balance between observable and unobservable matter by developing a method to stop stagnation of scholarly. The goal is to create prophetic students.Fakultas Tarbiyah IAI Muhammadiyah Bima masih menggunakan buku referensi ilmu pendidikan yang notabene tidak mengandung unsur profetik secara eksplisit. Buku referensi merupakan sumber rujukan siswa untuk menemukan ilmunya, memperkaya khazanah keilmuan, dan membangun paradigma berpikirnya. Penelitian ini bertujuan untuk mengembangkan referensi Ilmu Pendidikan dengan mengintegrasikan nilai-nilai profetik. Penelitian pustaka ini menggunakan pendekatan filosofis dan sosiologis. Sumber datanya adalah buku ilmu pendidikan, buku-buku profetik, dan lain-lain. Hasil penelitian menunjukkan bahwa rekonstruksi buku referensi ilmu pendidikan dengan nilai-nilai profetik mampu membentuk manusia yang beradab, berpendidikan dan berperilaku baik sebagai manusia. Selain itu, hal tersebut juga mengoptimalkan kapasitas kritis dan kreatif siswa, melahirkan sistem berpikir dari belenggu budaya dan tradisi, dominasi kelas dan jenis kelamin, serta menghilangkan penindasan. Secara transendental, membangun batin mereka sebagai makhluk Tuhan yang harus bertanggung jawab atas diri sendiri, masyarakat, dan alamnya. Hal ini harus mampu menyeimbangkan antara materi yang dapat diamati dan yang tidak dapat diamati dengan mengembangkan metode untuk menghentikan stagnasi ilmiah. Tujuannya adalah untuk menciptakan siswa yang profetik.